1998
DOI: 10.1006/viro.1998.9351
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of E3-Deleted Bovine Adenovirus Type 3 Expressing Full-Length and Truncated Form of Bovine Herpesvirus Type 1 Glycoprotein gD

Abstract: Using the homologous recombination machinery of E. coli, a 1.245-kb deletion was introduced in the E3 region of bovine adenovirus 3 (BAV3) genomic DNA cloned in a plasmid. Transfection of the restriction enzyme-excised, linear E3-deleted BAV3 genomic DNA into primary fetal bovine retina cells produced infectious virus (BAV3. E3d), suggesting that all the E3-specific open reading frames are nonessential for virus replication in vitro. Using a similar approach, we constructed replication-competent (BAV3.E3gD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 28 publications
0
65
1
Order By: Relevance
“…Previously, we have shown that intranasal immunization of cotton rats with recombinant adenovirus expressing a soluble form of the BHV-1 gD protein induced a higher antibody response than immunization with the virus expressing the membrane-anchored form of the protein (Zakhartchouk et al, 1998). However, in the present study, we demonstrated that pcDNA-St induced lower immune responses in vaccinated mice than pcDNA-SS.…”
Section: Discussioncontrasting
confidence: 82%
“…Previously, we have shown that intranasal immunization of cotton rats with recombinant adenovirus expressing a soluble form of the BHV-1 gD protein induced a higher antibody response than immunization with the virus expressing the membrane-anchored form of the protein (Zakhartchouk et al, 1998). However, in the present study, we demonstrated that pcDNA-St induced lower immune responses in vaccinated mice than pcDNA-SS.…”
Section: Discussioncontrasting
confidence: 82%
“…The E3 region of adenovirus is not essential for viral replication in tissue culture, but it is reported that E3 is involved in the regulation of immune response in vivo [34,35]. The deletion of E3a has been reported to enhance pulmonary lymphocyte infiltration when the deleted virus was administrated intranasally in cotton rats [36].…”
Section: Discussionmentioning
confidence: 99%
“…Replication-competent recombinant adenoviruses of several different species have been developed by homologous recombination, with insertion of foreign genes into the non-essential E3 region (Morrison et al, 2002;Zakhartchouk et al, 1998). The present study, however, used a different approach.…”
Section: Discussionmentioning
confidence: 99%